Genetic engineering : a primer - Hill, Walter E. 1937- (CRC Press, 2019)
Genetic Engineering: A Primer presents the growing field of biotechnology to non-science majors and other general interest readers. The author examines the natural forces that change genetic information and the ways in which scientists have learned to engineer these genetic changes. With a wealth of information flooding the popular press, including - Resumé vydavatel
"This edition first published 2002 by Taylor & Francis."
Includes index.
Keywords: genetické inženýrství; genetic engineering; elektronické knihy; monografie; electronic books; monographs